Modification of steel with barium and strontium - Rozhikhina I. D. Irina Dmitrievna; Nokhrina O. I.; Dmitrienko V. I. Vladimir Ivanovich; Platonov M. A. Maksim Aleksandrovich (2015, 2015)
Title screen